The Role Of Social Media Marketing In Building Brand Awareness And Brand Engagement (Empirical Study In Bittersweet By Najla Products) - Syahrani Syahrani; Raden Roro Roostika (UNIVED Press, 2026)
This study aims to analyze the role of marketing through social media in building brand awareness and brand engagement towards the purchase decision of Bittersweet by Najla products. In the digital age, social media marketing is an important strategy to increase consumer visibility and engagement with brands. This study uses a quantitative approach with a survey method through the distribution of online questionnaires to 225 respondents who are active social media users and have experience interacting with the Bittersweet by Najla brand. Data analysis was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 3.2.9 software.The results of the study show that marketing on social media has a positive and significant effect on brand awareness and brand engagement. In addition, brand awareness and brand engagement have been proven to have a significant influence on purchase decisions. These findings confirm the importance of optimizing social media marketing strategies to increase consumer loyalty and buying interest. This research is expected to contribute to the development of literature in the field of digital marketing and become a strategic reference for business people, especially the culinary sector in designing effective marketing campaigns.